Dampak Pemasaran Digital terhadap Keputusan Berkunjung Wisatawan di Kawasan Cisema - Napu, Della Maghfira; Nurhidayat, Wildan; Novianti, Fitria; Maelani, Ika; Rahma, Nadhifa Azaria (Jurnal Ilmu Manajemen, 2024)
Digital marketing is a type of promotion that is currently widely used by the public to support the various needs and needs that they carry out. The utilization of information gathering and promotion techniques through digital marketing can encourage someone to visit a tourist attraction or even to complete a transaction. This study aims to examine the impact of digital marketing on tourists' visiting decisions in the Cisema area. The research we use is of an exploratory type. This research was conducted at the Cisema tourist attraction, Sumedang district, to produce respondent data from 100 respondents. Using a nonprobability sampling method and also using a purposive sampling technique. Data was taken by distributing questionnaires and literature studies by processing data using SPSS version 25.0 through the stages of validity, reliability, coefficient of determination test, F-test table, T-test table, and also using path analysis techniques. From the results of this research, it can be concluded that digital marketing has a significant influence on the decision to visit tourists. It is hoped that the promotion and participation of the community and the government will be further enhanced and the government can facilitate the internet for the community and the government together to carry out promotions regarding tourist attractions in the Cisema area